Effect of bulb size on some vegetative and flowering growth parameters of Onion (Allium cepa L.) - منصور, يوسف; متيادي بوراس ,; حسان خوجه, (Latakia University Journal -Biological Sciences Series, 2023)
This research has aimed to evaluate the influence of bulb size on some vegetative and flowering growth parameters of onion (Allium cepa L.). The study was conducted on a private farm in the Qadmous region in mid-October for 2020/2021 agricultural season. Salmoni onion variety was used in the study. The experiment was designed according to the complete randomized blocks design. The experiment included 3 treatments: T1: small bulb size (35-40 g), T2: medium bulb size (55-60 g), T3: large bulb size (75-80 g). With 3 replications and with 5 plants in the replication. The results showed that treatment T3 was significantly superior to other treatments for all studied vegetative parameters, where recorded higher leaf height (59.6 cm), leaf number (29 leaf/plant), pseudostem diameter (25.4 mm), Leaf area index (10270cm2), fresh weight of vegetative total (381 g), dry weight of vegetative total (21.7 g). Results also showed that treatment T3 was better than other treatments T1 and T2 for all studied flowering parameters, where it was the fastest appearance flower stalks (129.6 day), flower stalk height (98.7 cm), flower stalk number (5.6 stalk/plant), umbel diameter (9.2 cm), flowers number (1040 flower/umbel). While treatment T2 was significantly superior to treatment T1 for most studied parameters